2018
DOI: 10.1002/htj.21393
|View full text |Cite
|
Sign up to set email alerts
|

MHD boundary layer flow of SWCNT‐water and MWCNT‐water nanofluid over a vertical cone with heat generation/absorption

Abstract: The analysis is carried out to investigate the magneto hydro dynamics (MHD) boundary layer flow, heat and mass transfer characteristics of two carbon nanotubes, namely, single‐wall carbon nanotubes (SWCNTs) and multiwall carbon nanotubes (MWCNTs), with water as the base fluid by taking thermal radiation and chemical reaction into consideration. Suitable similarity conversions are employed to reduce nonlinear partial differential equations into the system of ordinary differential equations, and these equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that two volume fractions of the nanomaterials, 0.5% and 1%, are considered here. In order to determine density, specific heat, thermal conductivity and dynamic viscosity, the following equations are applied [33,34]:…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that two volume fractions of the nanomaterials, 0.5% and 1%, are considered here. In order to determine density, specific heat, thermal conductivity and dynamic viscosity, the following equations are applied [33,34]:…”
Section: Methodsmentioning
confidence: 99%
“…The density, heat capacitance, and thermal diffusivity which are denoted by ρ nf , ( c p ) nf , and α nf of nanofluid, respectively, are given 42 }ρnf=ρf()1ϕ+ρCNTϕ,ρcpnf=ρcpf()1ϕ+ρcpCNTϕ,αnf=knf/ρcpnf.. …”
Section: Formulationmentioning
confidence: 99%
“…Recently Mahabaleshwar et al [29] showed the effect of radiation on the Graphene Casson Nanofluid and the effect of CNTs modeled through a Newtonian fluid flow formulation. Recently Anusha et al [30], Vishalaksi et al [31], Senha et al [32] and several researchers in the following references [33][34][35][36][37][38][39][40] have discussed the flow of several nano liquids along various types of surfaces. The present paper aims at examining the fluid flow in SWCNT and MWCNT with the impact of the induced slip and inclined MHD.…”
Section: Introductionmentioning
confidence: 99%